Global access to COVID-19 vaccines: Challenges in production, affordability, distribution and utilisation - Andreas Stamm; Christoph Strupat; Anna-Katharina Hornidge (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The COVID-19 pandemic and the ongoing vaccination process calls for decisive, internationally coordinated and forward-looking action. We propose short-, medium- and long-term actions and emphasise that the political pressure for action should not only focus on short-term management, but on building long-term structures that are crucial to prepare for future epidemics or pandemics. Four key challenges need to be addressed in order to achieve global control of COVID-19 by using vaccines. First, vaccines need to be produced at scale; second, they should be priced affordably; third, they have to be allocated globally so that they are available where needed; and fourth, they have to be deployed and utilised in local communities. Challenges in production are producing some of the main bottlenecks, but the others - in particular vaccine scepticism and utilisation - need to be considered early enough to enable smooth global vaccination campaigns. Addressing the four key challenges, we recommend the following short, medium- and long-term actions. In the short term, we advise accelerating global vaccination efforts by scaling up financial support for the COVAX initiative. In the medium term, we suggest establishing regional production centres in priority countries, providing the necessary intellectual property through voluntary patent pools and fostering information campaigns and civil society participation to increase vaccination willingness and utilisation. In the long term, we recommend establishing Global Pandemic Centres of Excellence in all world regions - analogous to the CGIAR system in the agricultural sector - that are responsible for medical research, vaccine production, distribution and delivery.
Keywords: 330